2008
DOI: 10.1007/s10661-008-0483-3
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the effect of urban green areas on the heat island in Athens

Abstract: The role of urban green areas in the microclimatic conditions of cities, during summer, is investigated in this paper through monitoring campaigns carried out at the National garden, at the city centre of Athens. Two types of investigations were carried out: i) a microscopic one that investigated the thermal conditions inside the Garden and the immediate surrounding urban area and ii) a macroscopic one that compared the temperature profile of the Garden with that of the greater city centre area. It was conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(72 citation statements)
references
References 40 publications
0
56
0
7
Order By: Relevance
“…This lush vegetation essentially is the only ‗green' factor of the city and contributes substantially to the quality of life of Bishkek's residents. As ascertained by [1] and [2], vegetation affects urban climate by moderating temperature, increasing humidity, influencing wind speed and reducing noise. Further desirables are reduction of solar radiation, view screening and visual amenity.…”
Section: The Role Of Green Spaces In Bishkekmentioning
confidence: 99%
“…This lush vegetation essentially is the only ‗green' factor of the city and contributes substantially to the quality of life of Bishkek's residents. As ascertained by [1] and [2], vegetation affects urban climate by moderating temperature, increasing humidity, influencing wind speed and reducing noise. Further desirables are reduction of solar radiation, view screening and visual amenity.…”
Section: The Role Of Green Spaces In Bishkekmentioning
confidence: 99%
“…On the one hand, they can contribute to improving environmental conditions through the reduction of air pollution (Nowak, Crane, & Stevens, 2006;Yang, McBride, Zhou, & Sun, 2004), regulating the micro-climates (Bernatzky, 1983;Dimoudi & Nikolopoulou, 2003), alleviating the heat island effect (Oliveira, Andrade, & Vaz, 2011;Zoulia, Santamouris, & Dimoudi, 2009), reducing the road traffic noise (Van Renterghem & Botteldooren, 2009), and preventing local floods caused by stormwater runoff from impervious surfaces (Dietz, 2007). Nevertheless, on the other hand, green spaces are high-required workforce activities (McPherson, 1992;McPherson, Simpson, Xiao, & Wu, 2011) so that a complex and professional approach is needed to protect workers and residents during all phases of these work sites (Rahardjo et al, 2009;Ricard & Bloniarz, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, the built environment-green areas interactions influencing the green cooling effects depend also on other elements related to urban form and geometry, such as building density, buildings height, width of streets, building orientation (Zhou et al, 2011;Li et al, 2012;Zoulia et al, 2009;David Suzuki Foundation, 2015). For instance, by considering different spatial resolutions (Li et al, 2012;Li et al, 2013), found that the percentage of cover of green space is correlated negatively with land surface temperature and that, the more closely linked and continuous the green spaces are, the stronger the cooling effect is.…”
Section: Introductionmentioning
confidence: 99%